Baseline Values of Left Ventricular Systolic Function in Preterm Infants With Septic Shock: A Prospective Observational Study - Zhong, Junjuan; Shuai, Chun; Wang, Yue; Mo, Jing; Ma, Dongju; Zhang, Jing; Lin, Yingyi; Yang, Jie; Ye, Xiuzhen (Frontiers in Pediatrics, 2022)
Background and Aim: The current guidelines recommended that cardiac index(CI) should achieve the target level of 3.3-6.0L/(kg·m2) in term infants with septic shock. However, it has not been recommended by guidelines in preterm infants with septic shock. The aim of this study was to investigate functional echocardiographic baseline values of left ventricular(LV) systolic functional parameters at onset of septic shock in preterm infants, and possible correlations between baseline values and poor outcomes. Materials and Methods: This was a prospective, observational, and longitudinal single-center study. Eligible infants were monitored for LV systolic functional parameters using functional echocardiography at onset of septic shock. The primary study outcome was differences in the baseline values of LV systolic functional parameters in preterm infants with septic shock of different gestational age(GA) and birth weight(BW), and the secondary outcome was septic shock-associated death or severe brain injury(including grade 3-4 intraventricular hemorrhage or periventricular leukomalacia). Results: In total, 43 subjects met the criteria, with a median GA of 321/7 weeks and BW of 1800 grams. No difference was observed in baseline values of LV systolic functional parameters among infants with septic shock of different GA and BW. Based on septic shock-associated death or severe brain injury, infants were assigned into good and poor outcomes. Twenty-nine(67.4%) infants out of 43 preterm infants had good outcomes, and 14(32.6%) infants had poor. Stroke index(SI) (18.2 vs 23.5, p=0.017) and cardiac index(CI)(2.7 vs 3.4, p=0.015) in infants with poor outcomes were significantly lower. Receiver operating characteristic(ROC) curve analysis showed that the cut-off value of SI and CI to predict poor outcomes in preterm infants with septic shock were 19.5mL/m2 (sensitivity, 73.9%; specificity, 81.8%) and 2.9L/(kg·m2) (sensitivity, 78.3%; specificity, 72.7%), with area under the ROC curve(AUC) value of 0.755 and 0.759, respectively. Conclusions: Preterm infants with septic shock of different GA and BW did not show significant difference in baseline values of LV systolic functional parameter. In the present study, however, we found that preterm infants whom SI＜19.5mL/m2 and/or CI＜2.9L/(kg·m2) at onset of septic shock are a group at high risk for poor outcomes.